Short Communication: Ethnobotanical and ecological studies of medicinal plants in a mangrove forest in Mempawah District, West Kalimantan, Indonesia - Yanieta Arbiastutie; Farah Diba; Masriani Masriani (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Arbiastutie Y, Diba F, Masriani. 2021. Short Communication: Ethnobotanical and ecological studies of medicinal plants in a mangrove forest in Mempawah District, West Kalimantan, Indonesia. Biodiversitas 22: 3164-3170. The mangrove forest Polaria Tanjung Pagar in Mendalok Village, Mempawah District, West Kalimantan, Indonesia, is a mangrove forest maintained by the local community. Currently, this mangrove forest has become one of the tourist attractions, not only visited by local and national, but also foreign tourists. This study aims to identify plants in Polaria Tanjung Pagar mangrove forest Kalimantan with the potential for medicinal uses. The research used a survey method in the mangrove forest by conducting an inventory of the medicinal plants found in the mangrove forest. Observations were made using a transect line with the total area understudy of 0.012 ha and sampling intensity of 0.4%. The investigation was based on cross-checking the traditional use of medicinal plants by the surrounding communities and the scientific literature. The results showed 13 types of medicinal plants (including tree and understorey plants) from 6 different families, i.e., Acrostichum aureum, Aegiceras corniculatum, Avicennia marina, Avicennia alba, Bruguiera parviflora, Bruguiera gymnorrhiza, Bruguiera cylindrica, Ceriops decandra, Rhizophora apiculata, Rhizophora stylosa, Rhizophora mucronata, Xylocarpus moluccensis, and Sonneratia caseolaris. The community structure of the mangrove forest had moderate diversity for tree species and low diversity for understorey plant species, with an H' valued at 2.39 and 0.25, respectively.